Spatial Heterodyne Offset Raman Spectroscopy Enabling Rapid, High Sensitivity Characterization of Materials' Interfaces. Issue 24 (19th May 2021) - Cui, Han; Glidle, Andrew; Cooper, Jonathan M.
Abstract: Spatially offset Raman spectroscopy is integrated with a fiber‐coupled spatial heterodyne spectrometer to collect Raman spectra from deep within opaque or scattering materials. The method, named spatial heterodyne offset Raman spectroscopy generates a wavenumber‐dependent spatial phase shift of the optical signal as a "spectral" image on a charge‐coupled device detector. The image can be readily processed from the spatial domain using a single, simple, and "on‐the‐fly" Fourier transform to generate Raman spectra, in the frequency domain. By collecting all of the spatially offset Raman scattered photons that pass through the microscope's collection objective lens, the methodology gives an improvement in the Raman sensitivity by an order of magnitude. The instrumentation is both mechanically robust and "movement‐free, " which when coupled with the associated advantages of highly efficient signal collection and ease of data processing, enables rapid interfacial analysis of complex constructs based on established biomaterials models. Abstract : Spatial heterodyne offset Raman spectroscopy is a technique which can be implemented as a simple, compact instrument in order to collect undistorted Raman spectra from deep within biomaterials with minimal signal processing. The method, which improves the sensitivity by an order of magnitude, is validated through high throughput measurements using model phantom systems.